Species diversity, stand productivity, aboveground biomass, and economic value of mangrove ecosystem in Mentawir Village, East Kalimantan, Indonesia - ROCHADI KRISTININGRUM; ABUBAKAR M. LAHJIE; MASJAYA; SYAHRIR YUSUF; YOSEP RUSLIM (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kristiningrum R, Lahjie AM, Masjaya, Yusuf S, Ruslim Y. 2019. Species diversity, stand productivity, aboveground biomass, and economic value of mangrove ecosystem in Mentawir Village, East Kalimantan, Indonesia. Biodiversitas 20: 2848-2857. Mangrove forest is one of the important ecosystems. It provides a variety of benefits both ecologically and economically. There are many biodiversity values of mangrove ecosystems that it can be evaluated economically. This study aims to: (i) identify the species diversity of mangrove forest; (ii) analyze the mangrove productivity and aboveground biomass; (iii) analyze the ecosystem value of mangrove forest in Mentawir Village, Penajam Paser District, East Kalimantan Province. The research used systematic random sampling method by establishing two plots with extent of one hectare for each plot in which each plot was divided into 20m x 20m subplots. The volume and mean annual increment (MAI), as well as current annual increment (CAI), were calculated. Economic value of mangrove ecosystem was calculated using Contingent Valuation Method (CVM) to reveal the total margin between Willingness to Pay (WTP) of wood produced by mangrove forest and Willingness to Accept (WTA) of fisheries catches. The results showed that there were 12 species of mangroves in the studied areas in which Rhizophora apiculata was the dominant species. Total aboveground biomass in Plot I and Plot II were respectively 127.46 tons ha-1 (62.61 tons C ha-1) and 79.26 (38.85 tons C ha-1) and dominated by Rhizophoraceace family with 76.80%, while 23.22% of the biomass was contributed by other mangrove families. The mangrove forest had a maximum average volume increment at 48 years and 42 years with MAI of 2.97 ha-1yr-1and 2.12 m3 ha-1yr-1 at Plot I and Plot II, respectively, with the total volume reached 127.5 m3 ha-1 and 79.60 m3 ha-1. The calculation of total margin between WTP and WTA indicated that in economic value of mangrove ecosystem in Mentawir Village with an extent of 2,300 ha was between IDR 207,000,000 yr-1 and IDR 345,000,000 yr-1. Our findings suggest that a good mangrove ecosystem will result in high economic value and biodiversity values cannot be separated from economic benefits in order to protect its sustainability.